Life cycle analysis approach to comparing environmental impacts of alternative materials used in the construction of small wastewater treatment plants - Pryce, David; Memon, Fayyaz Ali; Kapelan, Zoran (Environmental advances, 2021)
•Of investigated materials, stainless steel has the highest environmental impact.•Alternative materials offer considerably reduced environmental impact.•High Density Polyethylene was found to have the least environmental impact. With the aim of reducing the environmental burden of decentralized wastewater treatment plants in India, this project investigated five primary materials (stainless steel (SS), mild steel (MS), glass fibre reinforced polymer (GFRP), high density polyethylene (HDPE), and reinforced concrete cement (RCC)) in terms of the relative environmental impact that each would incur across 13 midpoint and 4 endpoint impact categories during the early life stages. The results showed that SS demonstrated substantially higher impact in total (5.47 Pt) and across each of the endpoint categories, most notably human health (3.12 Pt). Further investigations demonstrated that this was largely fed by the respiratory inorganics midpoint category that accounted for 50 % of the total impact (2.75 Pt), while global warming (0.93 Pt), non-renewable energy (0.70 Pt) and terrestrial ecotoxicity (0.62 Pt) were the only other considerable impacts. GFRP incurred the second greatest impact overall (2.32 Pt), while MS, RCC and HDPE followed with 1.82 Pt, 0.78 Pt, and 0.39 Pt respectively. HDPE afforded the greatest efficiency in all midpoint categories except carcinogens where RCC incurred the least environmental cost. Results were then compared with previous work and likely causal factors highlighted. Further study is recommended to investigate the longevity of the alternative materials in a wastewater containment role to support these results. [Display omitted]